(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
When using the names of flower species to create or describe an artistic image in poetry, the transfer of its meaning to a person is necessarily based on certain conditional similarities between a flower and a person. Such comparisons, a phenomenon of metaphorization, are also used to describe human emotions. This article discusses the “emotion is a plant” model that is observed in English and Uzbek poetry.